Хімічні перетворення і властивості проміжних фаз у багатокомпонентних РЗЕ-вмісних системах нітратних прекурсорів у ході оброблення з тепловою активацією - Дрючко, Олександр Григорович; Стороженко, Дмитро Олексійович; Бунякіна, Наталія Володимирівна; Іваницька, Ірина Олександрівна (НТУ "ХПІ", 2017)
У водно-сольовій системі KNO₃ – Mg(NO₃)₂ – Nd(NO₃)₃ – H₂O, як модельній системі нітратних прекурсорів РЗЕ й елементів ІА, ІІА груп періодичної системи, встановлено посилення комплексоутворюючої здатності Nd³⁺ активацією нагріванням. Конкуруючі процеси заміщення молекул H₂O на NO₃⁻ -групи в оточенні Ln³⁺ створюють умови для утворення відповідних високосиметричних аніонних комплексів. З’ясовується можливість використання впливу особливостей процесів структуро- і фазоутворення у таких системах на хід формування і відтворення структурочутливих характеристик цільових продуктів.

In multicomponent water-salt system KNO₃ – Mg(NO₃)₂ – Nd(NO₃)₃ – H₂O, as a model system of the REE nitrate precursors and elements of IA, IIA groups of the periodic system, which is currently being widely used in the synthesis of functional materials for various purposes, discovered an amplification of complexing ability of Nd³⁺- activated by heating. Competing processes of H₂O molecules replacement with NO₃⁻-groups surrounded by Ln³⁺ create conditions for the formation of the corresponding high-symmetry anionic complexes. The factors influencing the complexation of Ln have been studied. All identified nitrates complex were synthesized in the form of a single crystal. Was conducted a study of their atomic-crystalline structure, forms of coordination polyhedra, such as coordination ligands, and a number of other properties with the help of chemical, X-ray phase analysis, X-ray structural analysis, the second harmonic generation of laser radiation, infrared spectroscopy, thermography and other methods. For Ln³⁺ ionscomplex formers established tendency to form a limited number of types of coordination polyhedra, three types of coordination NO₃⁻-ligand. Coordination numbers of Nd³⁺ (Ln³⁺ cerium subgroup) in potassium compounds 12. Discovered the influence of the nature of Me⁺, Mg²⁺ on the form of coordination polyhedra, method of packaging systems in the spatial structure, properties of the compounds. It turns out the possibility of using the influence of the processes of structure and phase formation in such systems the formation and reproduction of the structure-sensitive characteristics of the target products.
Chemical transformations and properties of intermediate phases in multi-component REE-containing systems of nitrate precursors during processing with heat activation
Keywords: елементи рідкоземельні; неодим; калій; магній; нітрати; комплектоутворення; система водно-сольова; rare earth elements; neodymium; potassium; magnesium; nitrates; complexing; water-salt system